DEVELOPMENT OF THE SWARA AUGMENTED REALITY APPLICATION FOR WASTE SORTING EDUCATION IN ELEMENTARY SCHOOLS - Syahbaniar Rofiah; Endang Retnoningsih (LPPM Nusa Mandiri, 2026)
The prevailing issue of suboptimal waste management significantly contributes to environmental pollution. While early environmental education is crucial for instilling the habit of waste sorting, conventional methods often fail to engage elementary school students. To address this, this study developed an innovative learning medium integrating Augmented Reality (AR) to provide a more interactive and enjoyable learning experience. This research employed using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Initial Analysis identified user needs, leading to the Design of an application incorporating AR for interactive visualization for waste classification and marker creation. This development resulted in the